Efforts to Develop Students' Religious Character through the Habituation of Qur’anic Literacy in Vocational High Schools - Daffa Izzulhaq; Hafidz Hafidz (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to describe and analyze the efforts to develop students' religious character through the habituation of Qur’anic literacy at SMK Adi Sumarmo Colomadu (Adi Sumarmo Colomadu Vocational High School). This research used a qualitative approach in the form of field research. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the Miles and Huberman model (data reduction, data display, and verification). The results of the study show that the habituation of Qur’anic literacy is carried out regularly every morning by reading one rukuk before learning begins, to instill religious values through the practice of reading and understanding the Qur’an. This has a positive impact, manifesting in an increased habit of reading the Qur’an, improved quality of recitation, emotional calmness among students, and the internalization of religious values in daily life, thereby fostering a religious character in students. The supporting factors of this habituation include synergy between the principal, teachers, and students, as well as the availability of supporting facilities such as the mushaf and speakers in each classroom. The inhibiting factors include variations in Qur’anic reading ability among students and time constraints due to a dense academic schedule